2017
DOI: 10.1007/s40626-017-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with abiotic stresses: an integrative view of how phytohormones control abiotic stress-induced oxidative stress

Abstract: There is a very effective cross-talk between signals triggered by reactive oxygen species and the hormonal response in plants, inducing the expression of genes or activating proteins/enzymes likely to be involved in stress tolerance. Although abiotic stress responses and the role of the antioxidant system have been well explored in the literature, the understanding of the interrelationship between hormones and their effects on antioxidant system is not clear or well investigated. We attempted to scan the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 164 publications
0
14
0
Order By: Relevance
“…The most pronounced effects are various growth alterations, directly influenced by PGRs (Guo et al 2020;Wiszniewska et al 2019). Growth regulators control also the activation and efficiency of the general stress defense reactions (Julkowska and Testerink 2015;Sharma et al 2019;Souza et al 2017). Salinity leads to modifications in signal transduction of growth promoting as well as stress hormones, which may promote activation of specific protective mechanisms (Eyidogan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most pronounced effects are various growth alterations, directly influenced by PGRs (Guo et al 2020;Wiszniewska et al 2019). Growth regulators control also the activation and efficiency of the general stress defense reactions (Julkowska and Testerink 2015;Sharma et al 2019;Souza et al 2017). Salinity leads to modifications in signal transduction of growth promoting as well as stress hormones, which may promote activation of specific protective mechanisms (Eyidogan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is clear that this element is important to the biological process. However, it is frequently reported that metal excess can disrupt any of the processes mentioned above (Vernay et al 2007;González-Mendoza et al 2013;Panda et al 2015) and the way that an excess of metals can exert their toxicity is by direct interaction with non-target proteins or molecules, as well as by indirectly promoting an excess of reactive oxygen species (ROS) production (Souza et al 2017). For a phytoremediation purpose, it is interesting that photosynthesis shows stability during the stress event when plants are able to keep their growth under unfavourable conditions such as metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, all types of phytohormones, both growth promoters (auxins AUX, cytokinins CYT, gibberellins GAs) and inhibitors/regulators (abscisic acid ABA, jasmonic acid JA), as well as brassinosteroids (BR) and strigolactones (SL) are potent priming agents. On a molecular level, their stress-preventing action is attributed to signaling via phytohormonal cross-talks and interactions with the SSC synthesis pathways [ 49 ], regulation of gene expression, and influencing post-transcriptional protein modifications, as well as epigenetic control of stress-related genes [ 159 , 160 ]. Phytohormones are applied to plants via seed soaking, foliar spraying, and medium enrichment, with micromolar concentrations exerting a positive impact on plant functioning under metal exposure.…”
Section: Hydropriming Halopriming Hormopriming and Bioprimingmentioning
confidence: 99%